Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Guru SD Negeri Gugus 5 Kecamatan Palmerah Jakarta Barat - Saputri, Frizka Leoni; Karlina, Eulin (CV Warnak Johanna Nusantara, 2025)
The purpose of this research was to analyze the effect of Work Motivation and Work Dicipline on Teacher’s Performance at the Teacher of SD Negeri Gugus 5 Kecamatan Palmerah Jakarta Barat. In the process of implementing this research, the researcher used a type of quantitative research. The technique used in this study uses jenuh sampling. The number of respondents sampled in this study was 85 respondents. In addition, the data collection used by the researcher is by using observation, questionnaires, interviews and documentation. To be able to test the instrument using validity and reliability tests. The data analysis technique uses multiple regression. The results of this research are (1) Work motivation has positive effect on teacher’s performance (2) Work dicipline has positive effect on teacher’s performance (3) Work motivation and work dicipline together have a positive effect on teacher’s performance.